2017
DOI: 10.18632/oncotarget.16973
|View full text |Cite
|
Sign up to set email alerts
|

Association between metformin and the risk of gastric cancer in patients with type 2 diabetes mellitus: a meta-analysis of cohort studies

Abstract: ObjectivesThe objective of this study was to evaluate the association between metformin therapy and the incidence of gastric cancer (GC) in patients with type 2 diabetes mellitus (T2DM).MethodsWe systemically searched the following databases for studies published between the databases’ dates of inception and Nov. 2016: PubMed, Embase, the Cochrane Library, the Web of Science, and the China National Knowledge Infrastructure (CNKI). Hazard ratios (HR)and corresponding 95% confidence intervals (CIs) for the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 55 publications
0
38
0
Order By: Relevance
“…When compared to individuals with HbA1c levels of 5.0-5.9% [31-41mmol/mol], those with HbA1c levels of  6.0% [42mmol/mol] had more than twofold increase in GC risk. 12 Furthermore, all existing studies failed to adjust for concomitant medication usage which may modulate GC risk including aspirin, 13 nonsteroidal anti-inflammatory drugs (NSAIDs), cyclooxygenase-2 (COX-2) inhibitors, statins, 14 metformin, 15 and proton pump inhibitors (PPIs). 16,17 Failure to adjust for potential chemopreventive agents could bias a positive association between DM and GC to null as a higher proportion of patients with DM may require aspirin, statins and metformin.…”
Section: By Triggeringmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to individuals with HbA1c levels of 5.0-5.9% [31-41mmol/mol], those with HbA1c levels of  6.0% [42mmol/mol] had more than twofold increase in GC risk. 12 Furthermore, all existing studies failed to adjust for concomitant medication usage which may modulate GC risk including aspirin, 13 nonsteroidal anti-inflammatory drugs (NSAIDs), cyclooxygenase-2 (COX-2) inhibitors, statins, 14 metformin, 15 and proton pump inhibitors (PPIs). 16,17 Failure to adjust for potential chemopreventive agents could bias a positive association between DM and GC to null as a higher proportion of patients with DM may require aspirin, statins and metformin.…”
Section: By Triggeringmentioning
confidence: 99%
“…Metformin was associated with a lower GC risk in a meta-analysis. 15 Subgroup analysis was performed according to metformin use, glycemic control (i.e. timeweighted average HbA1c level) and cancer site (cardia and non-cardia).…”
Section: Subgroup Analysismentioning
confidence: 99%
“…While no association between metformin use and GC was reported by some studies, (10,11) others suggested a protective effect with varying effect estimates. (12)(13)(14)(15)(16) A recent meta-analysis (17) concluded that metformin decreased GC risk by 24% but there was a statistically significant heterogeneity among studies. More importantly, other important risk factors of GC including H. pylori infection and DM severity have not been adequately addressed in previous studies, potentially undermining the role of metformin on GC prevention.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, other important risk factors of GC including H. pylori infection and DM severity have not been adequately addressed in previous studies, potentially undermining the role of metformin on GC prevention. (17) As H. pylori is the most important risk factor of GC, failure to stratify patients according to H. pylori status will affect the true effect estimate of metformin on GC development. Moreover, GC risk was shown to be higher among individuals with higher hemoglobin A1c (HbA1c) levels (18).…”
Section: Introductionmentioning
confidence: 99%
“…Recently Zhou et al published a meta-analysis of seven cohort studies including a total of 591,077 diabetic patients (type 2). According to this study, the risk of developing a GC in metformintreated diabetic patients is significantly reduced (hazard ratio of 0.76) [21]. It was also demonstrated that survival rate of GC patients is increased in the diabetic patients group treated with metformin compared to the other diabetic patients, not treated with metformin [22].…”
mentioning
confidence: 53%